Transcriptome Response and Spatial Pattern of Gene Expression in the Primate Subventricular Zone Neurogenic Niche After Cerebral Ischemia - Chongtham, Monika C.; Wang, Haifang; Thaller, Christina; Hsiao, Nai-Hua; Vachkov, Ivan H.; Pavlov, Stoyan P.; Williamson, Lorenz H.; Yamashima, Tetsumori; Stoykova, Anastassia; Yan, Jun; Eichele, Gregor; Tonchev, Anton B. (Frontiers in Cell and Developmental Biology, 2020)
The main stem cell niche for neurogenesis in the adult mammalian brain is the subventricular zone (SVZ) that extends along the cerebral lateral ventricles. We aimed at characterizing the initial molecular responses of the macaque monkey SVZ to transient, global cerebral ischemia. We microdissected tissue lining the anterior horn of the lateral ventricle (SVZa) from 7 day post-ischemic and sham-operated monkeys. Transcriptomics shows that in ischemic SVZa, 541 genes were upregulated and 488 genes were down-regulated. The transcription data encompassing the upregulated genes revealed a profile typical for quiescent stem cells and astrocytes. In the primate brain the SVZ is morphologically subdivided in distinct and separate ependymal- and subependymal regions. The subependymal contains predominantly neural stem cells (NSC) and differentiated progenitors. To determine in which SVZa region ischemia had evoked transcriptional upregulation, sections through control and ischemic SVZa were analyzed by high-throughput in situ hybridization for a total of 150 upregulated genes shown in the www.monkey-niche.org image database. The majority of the differentially expressed genes mapped to the subependymal layers on the striatal or callosal aspect of the SVZa. Moreover, a substantial number of upregulated genes was expressed in the ependymal layer, implicating a contribution of the ependyma to stem cell biology. The transcriptome analysis yielded several novel gene markers for primate SVZa including the apelin receptor that is strongly expressed in the primate SVZa niche upon ischemic insult